Interesting Images: Endocytoscopy for In Vivo Diagnosis of Intestinal Graft-Versus-Host Disease - Timo Rath; Till Orlemann; Francesco Vitali; Abbas Agaimy; Andreas Mackensen; Markus F. Neurath (Diagnostics)
Gastrointestinal graft-versus-host disease (GvHD) is a frequent and severe complication after allogeneic stem cell transplantation (aSCTx). Although biopsy and histopathology remain the gold standard for diagnosis of GvHD, this approach can be limited by thrombocytopenia accompanying aSCTx and the diagnostic delay associated with routine histopathology. Here, we report on two patients in which dye-based contact microscopy using a latest generation endocytoscope with 520-fold magnification enabled in vivo diagnosis of GvHD. The first patient was a 23-year-old man with acute lymphoblastic leukemia presenting with non-bloody diarrhea 3 months after aSCTx. After topical staining with crystal violet and methylene blue, endocytoscopy in the rectum showed several apoptotic epithelial cells. Histopathology confirmed GvHD grade III according to the Lerner classification. The second patient was a 59-year-old female with diarrhea 3 months after aSCTx. Apart from pathognomic apoptotic bodies, EC additionally revealed crypt lumina enlargement and mononuclear cell infiltrates in the lamina propria with subsequent crypt distension. The duration of the procedure was less than 5 min in each patient. These findings illustrate that in vivo microscopy using endocytoscopy can enable instantaneous diagnosis of GvHD with the benefit of accelerating therapeutic decisions in patients with suspected severe GvHD.